TUNTUTAN GANTI RUGI ATAS TANAH YANG DIGUNAKAN UNTUK KEPENTINGAN UMUM DALAM MEMBANGUN WTP (WATER TREATMENT PLANT) DI PENGADILAN NEGERI TENGGARONG - Siti Rohaeti (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTThe process of land acquisition will never be separated by the existence of compensation issues. The deliberative mechanism which should be a means to find a middle ground in determining the amount of compensation often does not reach an agreement and hence for reasons of public interest, the government through the land acquisition committee can unilaterally determine the amount of compensation and then entrust it to the local district court. Land acquisition for the construction of WTP (Water Treatment Plant) is in the public interest.The problem examined in this study is how is the implementation process of the release of land rights for the construction of the WTP (Water Treatment Plant) and settlement of compensation for the land that has been carried out for the construction of the WTP (Water Treatment Plant). The method used in this study uses normative juridical research methods.The results of the study indicate that the legal arrangements regarding land acquisition for the public interest in the construction of the WTP (Water Treatment Plant) must be carried out by releasing land rights by providing compensation directly and through stages: determining the location, counseling, setting the boundaries, announcing the results, deliberation setting price, compensation, waiver. The government should provide compensation to the landowner in advance.Keywords: Compensation, Development, Public Interest.